Psychological Resilience Skills Training To Improve Psychological Resilience, Self Esteem, And Quality Of Life - Rita Benya Adriani; Jenita Doli Tine Donsu; Dwi Sulistyowati ((JKG) Jurnal Keperawatan Global, 2022)
Background: It is expected that the quality of life of TB patients will improve after treatment, but research shows indications of emotional stress in TB patients at the end of treatment, clinical, social consequences, drug resistance, and decreased quality of life, especially psychological and social aspects. Research purpose knowing the description of psychological resilience, self esteem, quality of life of TB survivors. Methods: A total of 61 TB survivors were taken by total sampling technique. 30 respondents in the experimental group were given psychological resilience skills training. Data was collected using the CD-RISC instrument, Rosenberg self-esteem scale, and WHOQOL-bref. Pre test is taken before training postData analysis used t test and regression test with SPSS 19 software. Results: Based on the SPSS analysis, it is known that no significant effect of psychological resilience on self esteem with p value of 0,33. Psychological resilience has a significant effect on quality of life with p value of 0,048. Self esteem has no significant effect on quality of life with p value of 0,335. Psychological resilience is more influential on social aspects than psychology on the quality of TB survivors. Conclussion: Possibly related to the participating in the association of fellow TB survivors. It can also caused by the length of time to recover. Psychological resilience skills can be developed by stakeholders for TB survivors.